Tumor-restricted activation of Vγ9Vδ2 T cells via bispecific Evobodies: a novel strategy for safe and potent immunotherapy in ovarian cancer - Oberg, Hans-Heinrich; Deseke, Malte; Krohn, Steffen; Winterberg, Dorothee; Peipp, Matthias; Bauerschlag, Dirk; Künkele, Klaus-Peter; Wesch, Daniela; Baumann, Christoph (Frontiers in Immunology, 2025)
IntroductionVγ9Vδ2 T cells have been clinically evaluated—both in vivo and ex vivo—for their efficacy against solid tumors over several decades. Although recent therapeutic approaches have renewed hope, significant and reproducible benefits for patients with solid tumors remains to be demonstrated.Material & MethodsWe have developed bispecific biologics in an IgG-extended format that bind both to Folate Receptor alpha (FOLR1), which is highly expressed in the majority of ovarian cancers, and to the activating butyrophilin (BTN)3A. By reducing the affinity of the BTN3A agonist and leveraging the increased avidity of the tetravalent, bispecific antibody, activation of BTN3A is restricted to FOLR1-positive tumors, thereby avoiding off-target activation of non-tumor cells.ResultsUsing RTCA co-culture assays with Vγ9Vδ2 T cells and tumor cell lines, we identified “Evobodies” that exhibit a strong therapeutic window and high potency against FOLR1-positive cells, while sparing healthy, FOLR1-negative tissue. Moreover, the lead molecule demonstrates high efficacy in a human autologous, patient-derived ex vivo tumor tissue model at unaltered/physiological effector-to-target (E:T) ratios. Importantly, we show that our tumor-engaging molecules avoid premature immune cell activation, degranulation, and cytokine release in the absence of FOLR1-positive tumor cells. They likely establish a cytokine gradient from the tumor site, harnessing the full potential of the natural local anti-infection response to target cancer cells.DiscussionThus, Evobodies represent a novel, first-in class of biologics for solid tumor treatment and are well-suited for further clinical development.